2019
DOI: 10.1002/cjoc.201900375
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting 2D Covalent Organic Frameworks: A New Opportunity for Efficient Solar Fuel Production

Abstract: Sustainable conversion of solar energy to chemical fuels via photocataytic processes represents an ideal solution to current energy and climate challenges. Thanks to their structural diversity and tunability as well as broad light absorption range, two‐dimensional covalent organic frameworks have emerged as promising candidates for photocatalytic solar fuel generation. This paper highlights recent advance in the development of two‐dimensional covalent organic frameworks for photocatalytic H2 evolution and CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
(8 reference statements)
0
9
0
2
Order By: Relevance
“…[ 5 ] Up to date, COF chemistry has shown generality of covalent linkages, [ 2,6‐20 ] diversity of pore engineering, [ 21‐23 ] and versatility in functional applications. [ 16,21,24‐34 ] Based on properties of large specific surface area, low density and tunable structures, it shows promising applications in fields of molecule storage and separation, [ 35‐39 ] catalysis, [ 40‐46 ] energy storage, [ 20,35,47‐49 ] optoelectronics, [ 50‐54 ] and so on. The development of this area relies much on understanding their crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Up to date, COF chemistry has shown generality of covalent linkages, [ 2,6‐20 ] diversity of pore engineering, [ 21‐23 ] and versatility in functional applications. [ 16,21,24‐34 ] Based on properties of large specific surface area, low density and tunable structures, it shows promising applications in fields of molecule storage and separation, [ 35‐39 ] catalysis, [ 40‐46 ] energy storage, [ 20,35,47‐49 ] optoelectronics, [ 50‐54 ] and so on. The development of this area relies much on understanding their crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) have been significantly developed as a novel class of porous organic polymers over the last 15 years. [ 1 ] Their highly ordered periodic two‐dimensional (2D) or three‐dimensional (3D) extended framework structures make them attractive crystalline porous materials with versatile applications, which range from gas storage [ 2 ] and separation, [ 3 ] heterogeneous catalysis, [ 4 ] chemosensing, [ 5 ] drug delivery, [ 6 ] proton conduction, [ 7 ] ion transport, [ 8 ] semiconductors, [ 9 ] to energy conversion [ 10 ] and storage. [ 11 ] These applications mainly benefit by their porosity, for which their porous structures, mainly pore shape and size, can be precisely pre‐designed and predicted.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[16][17][18][19] Previous studies revealed that the tri-s-triazine units in g-C 3 N 4 could facilitate the two-electron oxygen reduction by forming a complex with the O 2•− intermediate. [20][21][22] Despite the potential, their demonstrated photocatalytic activities were still unsatisfactory for practical applications.Covalent triazine frameworks (CTFs), as a new class of nitrogen-rich organic photocatalysts, have recently emerged owing to their excellent photocatalytic activities and stability for photocatalytic water splitting, [23][24][25][26] CO 2 reduction, [27][28] N 2 fixation, [29] and organic transformation. [30][31][32] In principle, their chemical and electronic structures can be precisely tuned by varying the corresponding precursors and synthetic routes, making them a versatile platform for designing photocatalysts on demand.…”
mentioning
confidence: 99%